Genetic counselling and high-penetrance susceptibility gene analysis reveal the novel CDKN2A p.D84V (c.251A>T) mutation in melanoma-prone families from Italy. Issue 2 (April 2017) - Borroni, Riccardo G.; Manganoni, Ausilia M.; Grassi, Sara; Grasso, Maurizia; Diegoli, Marta; Giorgianni, Carmela; Favalli, Valentina; Pavoni, Laura; Cespa, Maddalena; Arbustini, Eloisa
Abstract : Genetic susceptibility to primary cutaneous melanoma (PCM) may account for up to 12% of PCMs, presenting as the familial atypical mole/multiple melanoma syndrome (FAMMM), an autosomal dominant condition with incomplete penetrance and variable expressivity, characterized by PCM in at least two relatives and/or more than one PCMs in the same patient. To identify individuals at high genetic risk of PCM, from 1 January 2012 to 31 December 2015, we offered genetic counselling and molecular analysis of the two high-penetrance FAMMM susceptibility genes, cyclin-dependent kinase inhibitor 2A ( CDKN2A ) and cyclin-dependent kinase 4 ( CDK4 ), to 92 consecutive, unrelated patients with FAMMM. Age at diagnosis and number of PCMs were obtained from medical records; the number of PCMs and affected relatives were recorded for each family. The diagnostic work-up consisted of genetic counselling and cascade genetic testing in patients and further extension to relatives of those identified as mutation carriers. All exons and exon/intron boundaries of CDKN2A and CDK4 genes were screened by direct bidirectional sequencing. We identified CDKN2A mutations in 19 of the 92 unrelated patients (20.6%) and in 14 additional, clinically healthy relatives. Eleven of these latter subsequently underwent excision of dysplastic nevi, but none developed PCM during a median follow-up of 37.3 months. In three patients from unrelated families, the novel CDKN2A p.D84V (c.251A>T) mutation was observed, associated with PCM in each pedigree. Genetic screening of FAMMM patients and their relatives can contribute towards specific primary and secondary prevention programmes for individuals at high genetic risk of PCM. The novel CDKN2A p.D84V (c.251A>T) mutation adds to the known mutations associated with FAMMM.